Catalytic Activity of Cu/AC Catalyston Direct Synthesis of 1,1 Dibutoxybutane from 1-Butanol - Umam, Mukhamad Faeshol; Yoeswono (Pusat Pengembangan Sumber Daya Manusia Minyak dan Gas Bumi, 2024)
This study was conducted to investigate the catalytic activity of the Cu/AC catalyst in the direct synthesis of 1,1-dibutoxybutane (DBB) from 1-butanol. The Cu/AC catalyst was prepared through dry impregnation and characterized using TG/DTA, XRD, and SEM-EDS. The catalyst was placed in a continuous downflow quart tube reactor, and 1-butanol was pumped into a preheated reactor under an N₂ atmosphere at a specific temperature, contact time, reaction time, and 1-butanol concentration. The product was condensed and analyzed using FTIR, ¹H, ¹H-¹H COSY, ¹³C NMR, GC-MS, and GC. The results showed that the catalyst preparation procedure successfully impregnated Cu on the AC surface, and the resulting catalyst had catalytic activity in the direct synthesis of DBB from 1-butanol. As the temperature rises, the 1-butanol conversion and DBB selectivity increase. Longer contact and reaction times could lead to higher DBB concentrations. The concentration of 1-butanol in the feed affected the DBB concentration in the finished product. Higher conversion of 1-butanol is possible at a certain concentration. The addition of magnesium to the Cu/AC catalyst improved DBB formation. Although magnesium promoted butanal formation, DBB formation was more favorable on the Cu surface.